Gold nanoparticle-loaded porous poly(ethylene glycol) nanosheets for electrochemical detection of H2O2 - Zhao, Zhiyong; Zharnikov, Michael (Nanomaterials, 2023)
The effective detection of hydrogen peroxide (H2O2) in different environments and, above all, in biological media, is an important practical issue. To this end, we designed a novel electrochemical sensor for H2O2 detection by introducing gold nanoparticles (AuNPs) into the porous poly(ethylene glycol) (PEG) matrix formed by the thermally activated crosslinking of amino- and epoxy-decorated STAR-PEG precursors. The respective composite PEG-AuNP films could be readily prepared on oxidized Si substrates, separated from them as free-standing nanosheets, and transferred as H2O2 sensing elements onto the working electrode of the electrochemical cell, with the performance of the sensing element relied on the established catalytic activity of AuNPs with respect to H2O2 decomposition. The sensitivity, detection limit, and the operation range of the composite PEG-AuNP sensors were estimated at ~3.4 × 102 μA mM−1 cm−2, 0.17 μM of H2O2, and 20 μM-3.5 mM of H2O2, respectively, which are well comparable with the best values for other types of H2O2 sensors reported recently in literature. The particular advantages of the composite PEG-AuNP sensors are commercial source materials, a simple fabrication procedure, the bioinert character of the PEG matrix, the 3D character of the AuNP assembly, and the possibility of transferring the nanosheet sensing element to any secondary substrate, including the glassy carbon electrode of the electrochemical cell. In particular, the bioinert character of the PEG matrix can be of importance for potential biological and biomedical applications of the designed sensing platform.